(3efgL GdhUhd Edi JMQjQ GdaUhds - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3CMeO Hf OGhO Hf TQa GdOjf s)
(3ChdgG (B:s
(3bGd SjOfG RcQjG GdCfUGQi GdTGaYi hHYO aE(B^(3f GdaUhd GdegeI ai Yde ejQGK GdC(B/(3I ddEeGe GdgGFe GdTGaYi s
(3BNQgG (B:s
(3hgj ef GdeSGFd GdJi SCd YfgG CHh jhSa heMeO GdTGaYi QVi Gddg Yfg HeLdS GdQTjO , aCLGHgeG HPdc Je GdcJGH s
(3HGdfSNI BKGQ JeRjb ecedI ef fSNI CNQis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
Keywords: (3Yde GdaQGFVs